Respuesta :
Answer:
2, 4, 5, and 6 have the same pair of solutions.
Step-by-step explanation:
1. n(n+3)(n-4) = 0
2. 2n(4n+6)(6n-4) = 0
3. 2n(6-4n)(4n-6n) = 0
4. n(2n+3)(3n-2) = 0
5. 2n(2n+3)(3n-2) = 0
6. 3n(6n+9)(9n-6) = 0
Answers:
1. n = 0, -3, 4
2. n = 0, -3/2, 2/3
3. n = 0, 3/2
4. n = 0, -3/2, 2/3
5. n = 0, -3/2, 2/3
6. n = 0, -3/2, 2/3
Answer:
2,4,5,6
Step-by-step explanation:
[tex]n=0,4n+6=0\implies n=-\frac{6}{4}=-\frac{3}{2}[/tex]
[tex]6n-4=0\implies n=\frac{4}{6}=\frac{2}{3}[/tex]
n=0, [tex]n=-\frac{3}{2},n=\frac{2}{3}[/tex]
3.[tex]2n(6n-4)(4-6n)=0[/tex]
n=0
[tex]6n-4=0[/tex]
[tex]n=\frac{4}{6}=\frac{2}{3}[/tex]
[tex]4-6n=0[/tex]
[tex]n=\frac{4}{6}=\frac{2}{3}[/tex]
4.[tex]n(2n+3)(3n-2)=0[/tex]
[tex]n=0[/tex]
[tex]2n+3=0[/tex]
[tex]n=-\frac{3}{2}[/tex]
[tex]3n-2=0[/tex]
[tex]n=\frac{2}{3}[/tex]
5.[tex]2n(2n+3)(3n-2)=0[/tex]
[tex]n=0[/tex]
[tex]2n+3=0[/tex]
[tex]n=-\frac{3}{2}[/tex]
[tex]3n-2=0[/tex]
[tex]n=\frac{2}{3}[/tex]
6.[tex]3n(6n+9)(9n-6)=0[/tex]
[tex]n=0[/tex]
[tex]6n+9=0[/tex]
[tex]n=\frac{-9}{6}=-\frac{3}{2}[/tex]
[tex]9n-6=0[/tex]
[tex]n=\frac{6}{9}=\frac{2}{3}[/tex]
Answer:2,4,5 and 6 equation have same solutions.